Hypericin affects cancer side populations via competitive inhibition of BCRP - Vargová, Jana; Mikeš, Jaromír; Jendželovský, Rastislav; Mikešová, Lucia; Kuchárová, Barbora; Čulka, Ľubomír; Fedr, Radek; Remšík, Ján; Souček, Karel; Kozubík, Alois; Fedoročko, Peter (Biomedicine & pharmacotherapy, 2018)
OBJECTIVE: Cancer stem-like cells (CSLCs) are considered a root of tumorigenicity and resistance. However, their identification remains challenging. The use of the side population (SP) assay as a credible marker of CSLCs remains controversial. The SP assay relies on the elevated activity of ABC transporters that, in turn, can be modulated by hypericin (HYP), a photosensitizer and bioactive compound of St. John's Wort (Hypericum perforatum), a popular over-the-counter antidepressant. Here we aimed to comprehensively characterize the SP phenotype of cancer cells and to determine the impact of HYP on these cells. METHODS: Flow cytometry and sorting-based assays were employed, including CD24-, CD44-, CD133-, and ALDH-positivity, clonogenicity, 3D-forming ability, ABC transporter expression and activity, and intracellular accumulation of HYP/Hoechst 33342. The tumorigenic ability of SP, nonSP, and HYP-treated cells was verified by xenotransplantation into immunodeficient mice. RESULTS: The SP phenotype was associated with elevated expression of several investigated transporters and more intensive growth in non-adherent conditions but not with higher clonogenicity, tumorigenicity or ALDH-positivity. Despite stimulated BCRP level and MRP1 activity, HYP reversibly decreased the SP proportion, presumably via competitive inhibition of BCRP. HYP-selected SP cells acquired additional traits of resistance and extensively eliminated HYP. CONCLUSIONS: Our results suggest that SP is not an unequivocal CSLC-marker. However, SP could play an important role in modulating HYP-treatment and serve as a negative predictive tool for HYP-based therapies. Moreover, the use of supplements containing HYP by cancer patients should be carefully considered, due to its proposed effect on drug efflux and complex impact on tumor cells, which have not yet been sufficiently characterized.
Keywords: buněčné sféroidy; Cancer stem-like cells; analýza přežití; buněčné klony; ABC transportér z rodiny G, člen 2; nádorové buněčné linie; Neoplasm Proteins; Spheroids, Cellular; Perylene; St. John’s wort; ATP Binding Cassette Transporter, Subfamily B, Member 1; nádorové proteiny; substrátová specifita; Survival Analysis; ATP Binding Cassette Transporter, Subfamily G, Member 2; Side-Population Cells; Mice, SCID; Carcinogenesis; aldehyddehydrogenasa; anthraceny; Cell Line, Tumor; fenotyp; P-glykoprotein; Biomarkers, Tumor; Aldehyde Dehydrogenase; Neoplasms; Phenotype; nádorové biomarkery; zvířata; vedlejší populace buněk; Humans; Anthracenes; nádory; perylen; Substrate Specificity; Side population; ABC transporters; Drug resistance; Neoplastic Stem Cells; myši SCID; Hypericin; Clone Cells; karcinogeneze; nádorové kmenové buňky; lidé; Animals